Problematika Pendaftaran Jaminan Fidusia melalui Sistem AHU Online - Tsuroyyaa Maitsaa’ Jaudah (Universitas Muhammadiyah Magelang, 2024)
Electronic registration of fiduciary guarantees aims to enhance efficiency, transparency, and legal certainty, replacing the less effective manual methods. However, this system has shortcomings that hinder the registration process until the registration period expires. In the digital era, the application of technology in the legal system often faces obstacles, making it essential to improve efficiency and provide legal certainty. This research aims to identify the obstacles in electronic fiduciary registration using an empirical juridical method. The results show several technical issues that hinder the registration process until the registration period ends. The conclusion of this research suggests improvements to the AHU Online system and related policies so that the initial goals of electronic fiduciary registration, namely efficiency and legal certainty, can be better achieved.